Study protocol of an exercise and nutrition intervention for ovarian cancer patients during and after first-line chemotherapy (BENITA) - a randomized controlled trial - Tabea Maurer; M. H. Belau; B-C. Zyriax; G. Welsch; B. Jagemann; J. Chang-Claude; A. Daubmann; A. Buchholz; K. Glismann; A. Moeller; J. Sehouli; H. Woopen; et al. (BMC Cancer)
Abstract Background In ovarian cancer frequently reported side effects are muscle wasting and malnutrition, leading to frailty, decreased health-related quality of life (HRQoL), and cancer-related fatigue (CRF). Both often begin during first-line chemotherapy and develop progressively into a refractory state, if left untreated. Method Primary objective is to evaluate effectiveness of a newly developed app-based exercise and nutrition program under non-standardized conditions of clinical routine. We hypothize that patients who receive an individually tailored exercise and nutrition program for six months will have improved physical performance compared to patients who receive usual care. This is a multicenter randomized controlled open-label trial comparing an intervention group receiving a six-month exercise and nutrition intervention and a control group receiving usual care. Primary endpoint is the change in 6-Minute Walk Test (6MWT) from baseline to T2 (26 weeks after baseline) as a measure of physical functioning. Secondary endpoints include patients’ utilization and adherence to the nutrition program (MEDAS), their malnutrition risk (NRS2002), as well as patients’ HRQoL (see Table 1). Using the two-sample t-test with a two-sided type I error of 5% and 80% power, a medium effect size of Cohen’s d = 0.50 can be demonstrated with a minimum of 128 participants (64 per group). With a conservatively estimated dropout rate of 30%, 182 patients will be recruited. Patients who are included must be over 18 years of age, be diagnosed with ovarian cancer, cancer of fallopian tubes, or peritoneal cancer, FIGO stages II-IV, receive surgery and chemotherapy (adjuvant or neoadjuvant). Exclusion criteria are an ECOG status greater than 2, inadequate proficiency in German, or physical or mental impairments hindering the implementation of the program or execution of study procedures. Discussion In case of success, the project contributes in the long term to (i) improving medical care (diagnosis, psychoeducation, patient orientation, and empowerment), (ii) reducing the burden of disease and promoting physical autonomy for patients, and (iii) being incorporated into relevant guidelines. Trial registration The study was registered at ClinicalTrials.gov (NCT06250686).